2019
DOI: 10.2134/ael2018.11.0057
|View full text |Cite
|
Sign up to set email alerts
|

Rising Plate Meter Calibrations for Forage Mass of Wheat and Rye

Abstract: Estimating forage availability is important in optimizing livestock stocking rates. The rising plate meter was developed to estimate forage availability. It needs a calibration equation to convert its measurement to a prediction of forage mass, and predictions can vary across crops, seasons, and locations. Our research objective was to derive new calibration equations for wheat (Triticum aestivum L.) and rye (Secale cereale L.). Most past literature used a linear model, but recent literature has suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…Alfalfa's growth will slow and its con-tribution to the stand will decline in August, but an alfalfa stand will rebound and increase its contribution in the fall, as reported by Hendricks et al (2020). Furthermore, many of these calibration models are farm-or season-specific (Cho et al, 2019;Dillard et al, 2016;Sanderson et al, 2001).…”
Section: Comparing Nondestructive Sampling Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…Alfalfa's growth will slow and its con-tribution to the stand will decline in August, but an alfalfa stand will rebound and increase its contribution in the fall, as reported by Hendricks et al (2020). Furthermore, many of these calibration models are farm-or season-specific (Cho et al, 2019;Dillard et al, 2016;Sanderson et al, 2001).…”
Section: Comparing Nondestructive Sampling Proceduresmentioning
confidence: 99%
“…According to the results of the current work, a relatively large sample size is required to determine the canopy cover. The majority of forage research trials have found a 1-ft 2 quadrat to be sufficient for estimating HM (Cho et al, 2019;Dillard et al, 2016;Mason, 2020), whereas Baxter et al ( 2017) used a 10.7-ft 2 quadrat. The region's climate, coupled with the morphological characteristics of the ABG, resulted in a dense forage canopy with little bare ground, which saturated the images used in the ImageJ analysis.…”
Section: Implications and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The simple linear regression is a model that fit to predict the AHM in CH function. In fact, this is the most commonly used model for RPM calibration tests in different forage species (Michell, 1982;Michell and Large, 1983;Van der Colf, et al, 2013;Nakagami, 2016;Harmse et al, 2019;Cho, et al, 2019;Rayburn, 2020). Dillard et al (2016) evaluated the performance of the RPM in multispecies pastures composed of grasses, legumes and weeds, and reported that even, when equating the intercept to 0, the best prediction equation is a linear regression.…”
Section: Ch = Compressed Height (Cm)mentioning
confidence: 99%